Performance comparison of heat exchangers with different circuitry arrangements for active chilled beam applications - Chen, Can (2014)
This paper presents a performance comparison study of heat exchangers with different circuitry arrangements for active chilled beam (ACB) applications. Supported by a two-way discharge ACB terminal unit and a performance test pilot plant, four 2-rows plain fin and tube heat exchangers, namely, 1-circuit, 2-circuits, 4-circuits, and 8-circuits, are investigated under a wide range of chilled water volume flow rates. The chilled water side thermal and hydraulic characteristics are evaluated. The heat transfer rates are compared under three sets of criteria: identical water volume flow rate, identical pressure drop, and identical pumping energy consumption. Meanwhile, the comparisons are also performed in terms of two non-dimensional parameters: heat exchanger effectiveness and performance index. The study shows that different circuitry arrangements should be preferred in different operation conditions and under different evaluation criteria, while the 2-circuits arrangement is the most comprehensive and reasonable option rather than the 1-circuit one that is widely used in all available ACB products.